Advances in the valorization of waste and by-product materials as thermal energy storage (TES) materials. (June 2016) - Gutierrez, Andrea; Miró, Laia; Gil, Antoni; Rodríguez-Aseguinolaza, Javier; Barreneche, Camila; Calvet, Nicolas; Py, Xavier; Inés Fernández, A.; Grágeda, Mario; Ushak, Svetlana; Cabeza, Luisa F.
Abstract: Today, one of the biggest challenges our society must face is the satisfactory supply, dispatchability and management of the energy. Thermal Energy Storage (TES) has been identified as a breakthrough concept in industrial heat recovery applications and development of renewable technologies such as concentrated solar power (CSP) plants or compressed air energy storage (CAES). A wide variety of potential heat storage materials has been identified depending on the implemented TES method: sensible, latent or thermochemical. Although no ideal storage material has been identified, several materials have shown a high potential depending on the mentioned considerations. Despite the amount of studied potential heat storage materials, the determination of new alternatives for next generation technologies is still open. One of the main drawbacks in the development of storage materials is their cost. In this regard, this paper presents the review of waste materials and by-products candidates which use contributes in lowering the total cost of the storage system and the valorization of waste industrial materials have strong environmental and societal benefits such as reducing the landfilled waste amounts, reducing the greenhouse emissions and others. This article reviews different industrial waste materials that have been considered as potential TES materials and have been characterized as such. Asbestos containing wastes, fly ashes, by-products from the salt industry and from the metal industry, wastes from recycling steel process and from copper refining process and dross from the aluminum industry, and municipal wastes (glass and nylon) have been considered. Themophysical properties, characterization and experiences using these candidates are discussed and compared. This review shows that the revalorization of wastes or by-products as TES materials is possible, and that more studies are needed to achieve industrial deployment of the idea.